Explicit wave phenomena to the couple type fractional order nonlinear evolution equations - Khatun, M. Ayesha; Arefin, Mohammad Asif; Uddin, M. Hafiz; Baleanu, Dumitru; Akbar, M. Ali; İnç, Mustafa (Elsevier, 2021)
We utilize the fractional modified Riemann-Liouville derivative in the sense to develop careful arrangements of space-time fractional coupled Boussinesq equation which emerges in genuine applications, for instance, nonlinear framework waves iron sound waves in plasma and in vibrations in nonlinear string and space-time fractional-coupled Boussinesq Burger equation that emerges in the investigation of liquids stream in a dynamic framework and depicts engendering of shallow-water waves. A decent comprehension of its solutions is exceptionally useful for beachfront and engineers to apply the nonlinear water wave model to the harbor and seaside plans. A summed-up partial complex transformation is correctly used to change this equation to a standard differential equation thus, many precise logical arrangements are acquired with all the free parameters. At this point, the traveling wave arrangements are articulated by hyperbolic functions, trigonometric functions, and rational functions, if these free parameters are considered as specific values. We obtain kink wave solution, periodic solutions, singular kink type solution, and anti-kink type solutions which are shown in 3D and contour plots. The presentation of the method is dependable and important and gives even more new broad accurate arrangements.
Keywords: Solitary wave solution; Riemann-Liouville fractional derivative; Space-time fractional coupled Boussinesq equation; Space-time fractional-coupled Boussinesq; Burger equation; The double-expansion method